Impact of Anti-CD20 therapies on the immune homeostasis of gastrointestinal mucosa and their relationship with de novo intestinal bowel disease in multiple sclerosis: a review - Quesada-Simó, A.; Garrido-Marín, A.; Nos, P.; Gil-Perotín, S. (Frontiers in Pharmacology, 2023)
Multiple sclerosis (MS) and inflammatory bowel disease (IBD) are autoimmune disorders characterized by inflammatory episodes affecting the brain and the gastrointestinal (GI) tract, respectively. The frequent association between MS and IBD suggests that both conditions may share common pathogenic mechanisms. However, different responses to biological therapies indicate differences in immune mechanisms of inflammation. Anti-CD20 therapies are high efficacy treatments increasingly used to control inflammatory bursts in MS, but they may alter GI homeostasis and promote the development of bowel inflammation in susceptible individuals. This review analyzes the mechanistic association between immunity in MS and IBD, the effect of anti-CD20 therapies on the gut microenvironment, and provides recommendations for early detection and management of GI toxicities in the context of B-cell depletion in MS patients.